Pattern of invasion in squamous cell carcinomas of the lower lip and oral cavity - Shahroo Etemad-Moghadam; Mojgan Alaeddini (Elsevier, 2017)
Background: A number of factors may be responsible for the differences in the biologic behaviors of oral and lower lip squamous cell carcinomas (SCCs). Immunohistochemical invasion profiles have been used to detect invasion patterns like epithelial-mesenchymal-transition (EMT) and collective-cell-invasion (CCI), which have not been investigated in lower lip neoplasms. The aim of the present study was to compare the invasive phenotypes of SCCs of the lower lip and oral cavity. Method: A total of 44 OSCCs and 37 lower lip SCCs were immunostained with E-Cadherin, N-Cadherin, and podoplanin. Based on their expression patterns, tumors were allocated to EMT, CCI or non-EMT/non-CCI categories. Results: None of the oral SCCs showed EMT; while 5 lower lip SCCs demonstrated this phenotype. CCI was observed in 12 oral SCCs and 4 lower lip SCCs. The third group included 32 and 28 cases of oral and lower lip tumors, respectively. A significant difference in invasive phenotype was found between the two locations (P = 0.009). Conclusion: Oral cavity and lip tumors differ in various aspects and according to our results; the pattern of invasion may be added to these features. Between the two major invasion patterns, EMT was more prevalent in lip tumors while CCI was observed more commonly in oral neoplasms. The significance of the different expression patterns of the non-EMT/non-CCI category requires further investigation.